Ez-CVal: auto generation of critical values - Michael, Roseline; Muhiddin, Fatihah Anas; Janteng, Janvin (Academica Press Solutions, 2023)
Critical values play an important role in hypothesis testing and confidence interval. Failure to read the critical values from a statistical table will lead to the wrong answer. One way to overcome this problem is by implementing interactive teaching styles. Advances in digital technologies provide support for ensuring educators have effective pedagogical tools and resources. Thus, an innovation that offers engaging tools can be used in the classroom to empower students' learning capabilities. However, an unreliable internet connection may ruin the learning process if online-based teaching tools are used in a physical classroom with a poor internet connection. Based on these factors, Ez-CVal was developed as a teaching and learning tool that can help educators create an immersive learning experience for students. With Ez-CVal, critical values can be generated automatically. Hence, the confidence interval can be constructed correctly, and the decision-making in hypothesis testing can be done more efficiently. Ez-CVal can be accessed via electronic mobile devices such as laptops. The design of this product was made to be user-friendly and easy to operate. This product also takes into account the aesthetic elements, where the colours can be provided according to the user's preference. Another uniqueness of this product is that it is an offline-based digital teaching tool that can be accessed without having to use the internet or have any additional software installed. Ez-CVal is expected to have a potential commercial value and can be used as a digital tool in teaching and learning statistics courses in any higher education institution.